2022
DOI: 10.1007/s13204-022-02608-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of in vivo toxicity of MgO/ZnO core/shell nanoparticles synthesized by eco-friendly non-thermal plasma technology

Abstract: MgO/ZnO core/shell nanoparticles were synthesized using the atmosphere plasma jets technique. The physical properties of the synthesized nanoparticles were investigated by a series of techniques, including X-ray diffraction (XRD), X-ray dispersive spectroscopy (EDS), and transmission electron microscopy (TEM). XRD and EDS analyses confirmed the purity of the nanoparticles synthesized with an average nanoparticle crystallite size of 36 nm. TEM confirmed the successful synthesis of spindle-shaped MgO/ZnO core/sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…As shown in Figure (1), the experimental setup for the fabrication of CuO nanostructures consisted of a high voltage DC power supply (20 kV), an argon gas cylinder, flowmeter, and two electrodes: a stainless steel tube as the cathode, and a copper foil (purchased from the british drug houses Ltd./london, Manufactured in England, 652247/470611) as the anode. The Cu foil was immersed in a glass beaker containing 5 ml of deionized water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure (1), the experimental setup for the fabrication of CuO nanostructures consisted of a high voltage DC power supply (20 kV), an argon gas cylinder, flowmeter, and two electrodes: a stainless steel tube as the cathode, and a copper foil (purchased from the british drug houses Ltd./london, Manufactured in England, 652247/470611) as the anode. The Cu foil was immersed in a glass beaker containing 5 ml of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, non-thermal plasma applications have developed significantly to include biomedical devices, biological materials, and material technologies [1]. The Atmospheric Pressure Plasma Jets (APPJs) are non-thermal plasmas with high electron and low gas temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Mohammed et al 2022a , b ) reported the synthesis of CuO/ZnO core/shell nanoparticles with argon plasma jets.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, the field of non-thermal plasma has expanded significantly. The topic of chemical interactions between non-thermal plasma and liquids attracted the attention of researchers due to its potential medical and economic benefits (Rumbach et al 2013 ; Mohammed et al 2022a , b ). Recently, nanomaterial (NM) synthesis through plasma–liquid interactions (PLIs) is a new branch of plasma research that has grown rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Using physical and chemical methods, nanoparticles of different materials have been created. Different techniques, such as pulsed laser deposition, thermal decomposition, hydrothermal procedures, sol-gel preparation, chemical coprecipitation, etc., may be used to create nanoparticles (Mohammed et al, 2022a;Abbasalipourkabir et al, 2015). Traditional methods have been used for years to generate NPs, but research has shown that green approaches are more effective and cheaper, with fewer failures and easier characterization.…”
Section: Introductionmentioning
confidence: 99%